2018
DOI: 10.1016/j.jasrep.2017.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Execution technique and pigment characteristics of Byzantine wall paintings of Anaia Church in Western Anatolia

Abstract: In this study, material characteristics of wall paintings executed in 11th Century Byzantine Church located in archaeological site of Anaia (Turkey) were investigated to provide historical information of the painting techniques. For this purpose, physical, chemical and mineralogical compositions of the paintings were determined by X-Ray Diffraction, Fourier Transform Infrared spectroscopy, Scanning Electron Microscopy coupled with Energy Dispersive spectroscopy and Thermo-Gravimetric Analysis. Analysis results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The dark border visible in the SEM-BSE microphotographs of green (G) and red (R1) cross sections could be ascribed to a discontinuity surface (Figure 7b,d, respectively). This sort of contact line is attested in the literature for Byzantine wall paintings and assigned to the application of paint on a dry wall [35], probably also in this case with lime binder, as inferable from the Ca-rich line sometimes visible on the top. The sharp contact between the pigmented layer and the substrate is evident also in OM images (Figure 7a,c) and in the iron distribution map (Figure 7e), especially if compared with those of the samples classified as a fresco (Figure 2a, Figure 3a,c and Figure 4).…”
Section: Painting Techniquementioning
confidence: 62%
“…The dark border visible in the SEM-BSE microphotographs of green (G) and red (R1) cross sections could be ascribed to a discontinuity surface (Figure 7b,d, respectively). This sort of contact line is attested in the literature for Byzantine wall paintings and assigned to the application of paint on a dry wall [35], probably also in this case with lime binder, as inferable from the Ca-rich line sometimes visible on the top. The sharp contact between the pigmented layer and the substrate is evident also in OM images (Figure 7a,c) and in the iron distribution map (Figure 7e), especially if compared with those of the samples classified as a fresco (Figure 2a, Figure 3a,c and Figure 4).…”
Section: Painting Techniquementioning
confidence: 62%
“…Although its colour is bright, its chemical property is unstable [60]. Discoloration and degradation are common in murals around the world [61][62][63]. Mogao Grottoes used minium extensively in the prosperous Tang Dynasty [64].…”
Section: Characteristics Of the Pigment Layermentioning
confidence: 99%
“…SEM-EDS and optical microscopy are particularly useful for observing the microscopic morphology and structure of painted artwork materials [14,15]. For example, in the case of the fresco sections in an Andean church, Tomasini et al [16] determined the morphological characteristics of the layers and the elemental composition using optical microscopy and SEM-EDS, and confirmed that the sequence of the fresco's sections began with the pigment layer lining the surface, followed by white ground layer applied above the adobe wall.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the case of the fresco sections in an Andean church, Tomasini et al [16] determined the morphological characteristics of the layers and the elemental composition using optical microscopy and SEM-EDS, and confirmed that the sequence of the fresco's sections began with the pigment layer lining the surface, followed by white ground layer applied above the adobe wall. In the study conducted by Demir et al [14], the painting techniques were also analyzed by optical microscopy and SEM-EDS, and the results indicated that the paintings were composed of a fine plaster and a thin paint layer over the plaster layer.…”
Section: Introductionmentioning
confidence: 99%